2021
DOI: 10.3389/fpubh.2021.723807
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the Acute Respiratory Infections and Associated Factors in the Rural Areas and Urban Slum Areas of Western Maharashtra, India: A Community-Based Cross-Sectional Study

Abstract: Acute respiratory infections (ARIs) continue to be the most important cause of morbidity and mortality among under-five children. Some demographic and environmental factors are associated with ARIs among under-five children. This study was conducted with the objective to estimate the prevalence of ARIs among under-five children in the rural areas and densely populated urban slum areas in Maharashtra, India and to assess the association of the selected sociodemographic and household environmental factors with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 19 publications
1
12
2
2
Order By: Relevance
“…On the other hand, the proportion is lower than other studies conducted in Gondar Comprehensive Specialized Hospital (27.3%) [21], Northwest Ethiopia (19.2%) [22], Wolaita Sodo [23], Dessie (42.82%) [24], Uganda (40.3%) [25], rural India (59.1%) [26], and India (50%) [27]. A possible reason for this variation might be the differences in study populations, study settings, age categories of study participants, method used to ascertain the outcome variable, comorbidities, variations in the study period, and season of the study.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…On the other hand, the proportion is lower than other studies conducted in Gondar Comprehensive Specialized Hospital (27.3%) [21], Northwest Ethiopia (19.2%) [22], Wolaita Sodo [23], Dessie (42.82%) [24], Uganda (40.3%) [25], rural India (59.1%) [26], and India (50%) [27]. A possible reason for this variation might be the differences in study populations, study settings, age categories of study participants, method used to ascertain the outcome variable, comorbidities, variations in the study period, and season of the study.…”
Section: Discussionmentioning
confidence: 64%
“…Flu, viruses, and bacteria are more likely to remain stable in the air as the temperature decreases, creating respiratory droplets and causing damage to the airways, allowing bacteria to produce infections, most often ARI in the lungs. Another explanation might be that many of the children in these areas were under the age of 1 year, and the majority of these homes relied on charcoal and cow dung for re [27,28]. Among women who had attended secondary education, acute respiratory infection was reduced compared to that in women who had no education.…”
Section: Discussionmentioning
confidence: 99%
“…23 , 24 Aside Cameroon which has 1% prevalence of ARI among the under-5 children, other studied countries had higher prevalence of the ARI but not as high as have been reported by studies in Nigeria, 25 Ethiopia 18 and another that comprised some African countries 7 as well as from a Nepalese 26 and an Indian studies. 27 The discoveries could be explained by inadequate wealth-related and education status of mothers, insufficient supply of water, the prevalence of communicable diseases, and poor nutrition knowledge, that are more predominant in many Sub-Saharan countries when compared to their developed counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of smokers in the house can cause recurrent ARI occurrences in toddlers. Supported by the results of research which states that cigarette smoke has a strong effect on the lungs of children under five, especially those who spend a lot of time indoors, causing an increased risk of recurrent ARI [30]. Research results Teijeiro, A., Cuello, M. N., et al [31] also showed that in the first 12 months 33% of 1062 children under five experienced a recurrence of cough.…”
Section: Risk Of Smoking Parentsmentioning
confidence: 95%